Analisis Respon Internal Penerapan e-SKA di Kementerian Perdagangan Menggunakan Pendekatan Mixed Methods - Indra Chaidir Chaidir; Deya Valensia Karolina; Alif Sofia Kusumawardani; Pudji Widodo (Universitas Bina Sarana Informatika, 2026)
This study was conducted to assess the responses of employees at the Ministry of Trade to the Electronic Certificate of Origin (e-SKA) system. The primary focus was to determine whether the system was perceived as easy to use and how beneficial it was in assisting their daily work. Furthermore, the study sought to identify the problems or obstacles employees frequently encountered when using the system. To obtain data, the study employed a mixed methods approach. The numerical data were obtained from questionnaires distributed to 39 employees, while direct interviews with system users were conducted for more in-depth explanation. The results indicated that the majority of employees were satisfied with and found the e-SKA system helpful, as it facilitated their work. However, interviews revealed that the system still frequently encountered technical glitches, lacked comprehensive features, and many employees felt they needed further training to address confusion. Despite these shortcomings, the system has been generally well-received by employees. Suggestions for the future include improvements to the technological devices used and the creation of clearer guidebooks or training so that employees can work more smoothly in processing certificates of origin in the future.